Asymmetric Response of the Biological Carbon Pump to the ENSO in the South China Sea. Issue 2 (18th January 2022) - Li, Hongliang; Zhang, Jingjing; Xuan, Jiliang; Wu, Zezhou; Ran, Lihua; Wiesner, Martin G.; Chen, Jianfang
Abstract: Biological carbon pump (BCP) inefficiency was first observed in the South China Sea (SCS) throughout the 1997–1999 El Niño Southern Oscillation (ENSO) event, but the BCP usually recovers its efficiency when the climate conditions change from El Niño to La Niña conditions in the Pacific Ocean. Enhanced stratification and Kuroshio intrusion led to weak mixing and oligotrophic conditions in the sunlit layer of the SCS during the 1997/1998 El Niño phase, but the particulate organic carbon (POC) flux was comparable to the climatological mean due to the ballast effect of increased lithogenic material and CaCO3 flux. The deepened thermocline rendered the recovered mixing less effective in replenishing subsurface nutrients and subsequently lowered POC flux during the 1998/1999 La Niña phase. Both scenarios were characterized by decreased siliceous plankton but a stimulated calcareous plankton contribution, which reduced BCP efficiency, resulting in a unique asymmetric response to the ENSO in the SCS. Plain Language Summary: The El Niño‐Southern Oscillation (ENSO) in the Pacific Ocean is one of the most important ocean‐atmosphere coupled climatic phenomena on Earth, and the ENSO in turn influences marine biogeochemical cycles and the biological carbon pump (BCP). Usually, as climate conditions transition from the El Niño to La Niña phases, the weakened BCP rebounds to a highly productive level in the central and eastern Pacific. However, the BCP exhibits an asymmetric response to the ENSO in the South China Sea (SCS), the largest tropical marginal sea of the Pacific Ocean. We show that strengthened stratification of the upper water column and enhanced oligotrophic Kuroshio intrusion led to impoverished in bioavailable nutrients near the surface, caused fewer siliceous plankton compared to calcareous plankton, and thus resulted in an inefficient BCP in the 1997/1998 El Niño phase. In contrast, the deepened thermocline prevented the replenishment of nutrients from the subsurface, subsequently inhibiting the rebound of primary production and deep biogenic flux during the 1998/1999 La Niña phase. This study may aid in understanding the response of the BCP to ENSO events in marginal seas and improve predictions of global ocean carbon storage. Key Points: The South China Sea biological carbon pump does not rebound from the 1997/1998 El Niño to La Niña phase as expected The enhanced stratification and Kuroshio intrusion are responsible for the low opal:CaCO3 ratio of sinking particles in the El Niño phase The deepened thermocline prevents the diapycnal nutrient supply and the recovery of the biological carbon pump in the La Niña phase